2019
DOI: 10.1108/ijchm-07-2017-0425
|View full text |Cite
|
Sign up to set email alerts
|

Building employees’ organizational citizenship behavior for the environment

Abstract: Purpose Mechanisms behind employees’ pro-environmental behaviors have increasingly been attracting scholarly attention. The purpose of this study is to examine how environmentally specific servant leadership contributes to employees’ organizational citizenship behavior for the environment (employee OCBE). Design/methodology/approach In this research, employees from resort hotels in Central Vietnam were selected as participants. The data analysis was conducted through structural equation modeling and bootstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 75 publications
8
120
1
1
Order By: Relevance
“…Findings revealed that the direct impact of servant leadership on EVGB was not supported. This result is inconsistent with the literature, where the direct or indirect effect of servant leadership was investigated on employees' organizational citizenship behavior for the environment [40][41][42], a construct similar to EVGB. The reason behind this finding is that both psychological empowerment and autonomous motivation for the environment fully mediates the influence of servant leadership on EVGB.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Findings revealed that the direct impact of servant leadership on EVGB was not supported. This result is inconsistent with the literature, where the direct or indirect effect of servant leadership was investigated on employees' organizational citizenship behavior for the environment [40][41][42], a construct similar to EVGB. The reason behind this finding is that both psychological empowerment and autonomous motivation for the environment fully mediates the influence of servant leadership on EVGB.…”
Section: Discussioncontrasting
confidence: 80%
“…The existing scholarship has established the positive influence of servant leadership on employees' psychological empowerment [61], intrinsic motivation [48], and employees' extra-role behaviors [42]. In the preceding sections of this article, it has been further accentuated that psychological empowerment and autonomous motivation for the environment would be the mechanisms through which servant leadership exerts its influence in predicting EVGB.…”
Section: Sequential Mediation Of Psychological Empowerment and Amementioning
confidence: 93%
See 2 more Smart Citations
“…Employee Organizational Citizenship Behavior supports the organization's performance (Luu, 2019). The Organizational Citizenship Behaviour value improves the performance of the employee and organization, and it is a terminology to identify employee behavior.…”
mentioning
confidence: 99%